2022
DOI: 10.1021/jacs.1c12764
|View full text |Cite
|
Sign up to set email alerts
|

Co-Solvent Electrolyte Engineering for Stable Anode-Free Zinc Metal Batteries

Abstract: Anode-free metal batteries can in principle offer higher energy density, but this requires them to have extraordinary Coulombic efficiency (>99.7%). Although Zn-based metal batteries are promising for stationary storage, the parasitic side reactions make anode-free batteries difficult to achieve in practice. In this work, a salting-in-effect-induced hybrid electrolyte is proposed as an effective strategy that enables both a highly reversible Zn anode and good stability and compatibility toward various cathode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
257
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(310 citation statements)
references
References 65 publications
8
257
2
Order By: Relevance
“…Furthermore, the cycled Zn electrode in 0.5 m TMP exhibits a higher intensity ratio of Zn(002) to Zn(100) than that in the aqueous counterpart (6.28 vs. 4.93), contributing to the dendrite-free behavior in 0.5 m TMP. In addition, the formulated 0.5 m TMP in this study compares favorably with recently reported electrolytes for Zn-based battery chemistries such as concentrated hydrous organic electrolytes, 36 anhydrous organic electrolytes, 33,35,37 deep eutectic electrolytes, 11,30,31,50 hybrid aqueous/organic electrolytes, 25,27,29 and concentrated dual salt electrolytes 19–21 (Fig. 5k).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, the cycled Zn electrode in 0.5 m TMP exhibits a higher intensity ratio of Zn(002) to Zn(100) than that in the aqueous counterpart (6.28 vs. 4.93), contributing to the dendrite-free behavior in 0.5 m TMP. In addition, the formulated 0.5 m TMP in this study compares favorably with recently reported electrolytes for Zn-based battery chemistries such as concentrated hydrous organic electrolytes, 36 anhydrous organic electrolytes, 33,35,37 deep eutectic electrolytes, 11,30,31,50 hybrid aqueous/organic electrolytes, 25,27,29 and concentrated dual salt electrolytes 19–21 (Fig. 5k).…”
Section: Resultssupporting
confidence: 82%
“…[16][17][18] Effective strategies to stabilize Zn anodes include designing highly concentrated aqueous electrolytes [19][20][21][22][23] and using aqueous-organic hybrid electrolytes. [24][25][26][27][28][29] Alternatively, exploring organic electrolytes would offer another opportunity to boost Zn reversibility because of the high thermodynamic stability of Zn in organic solvents. [30][31][32][33] However, nonaqueous RZBs oen employ solvents of acetonitrile (AN), 34,35 ethylene glycol (EG), 36,37 and carbonates, 38,39 which are highly ammable and pose safety hazards.…”
Section: Introductionmentioning
confidence: 99%
“…Z 1 W-0.2NMP extends the onset voltage of the oxygen evolution reaction near 2.7 V ( vs. Zn 2+ /Zn) with a set amount of NMP dilution, revealing that NMP participation has improved electrolyte stability and potentially prevented Zn parasitic reactions. 26 Fig. 3b–h show the CV, GCD, and cycling profiles of Z 1 W-0.2NMP assembled in Zn//active carbon (AC) coin cells, operating in the voltage range of 0.2–1.8 V. The following CV curves at different scan rates were obtained to indicate the reaction kinetics in the Z 1 W-0.2NMP electrolyte (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Ming et al discovered that in the presence of propylene carbonate, triflate anions are involved in the Zn 2+ solvation sheath structure, even at a low salt concentration (2.14 M). 127 The unique solvation structure results in the reduction of anions, thus forming a hydrophobic solid electrolyte interphase. The waterproof interphase along with the decreased water activity in the hybrid electrolyte effectively prevents side reactions, thus ensuring a stable Zn anode with unprecedented coulombic efficiency (99.93% over 500 cycles at 1 mA cm −2 ).…”
Section: Modifications Of Abesmentioning
confidence: 99%